2009
DOI: 10.1021/la9033723
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Templates and Ordered Liquid Bridge Networks in Evaporative Lithography

Abstract: We investigate the properties of latex particle templates required to optimize the development of ordered liquid bridge networks in evaporative lithography. These networks are key precursors in the assembly of solutions of conducting nanoparticles into large, optically transparent, and conducting microwire networks on substrates (Vakarelski, I. U.; Chan, D. Y. C.; Nonoguchi, T.; Shinto, H.; Higashitani, K. Phys. Rev. Lett., 2009, 102, 058303). An appropriate combination of heat treatment and oxygen plasma etch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 19 publications
2
39
0
Order By: Relevance
“…Vakarelski et al demonstrated formation of gold wires in am acroscale connected network using ac olloidal mask of latex beads. [36][37]45] Importantly,t he addition of surfactant was important to stabilize the liquid film and allow the formation of the plasmonic network upon drying (Figure 4A,B). In order to improvet he reproducibility and versatility,t he authors used ap hotoresist as am askt od irect the drying of the goldc olloid ( Figure 4C).…”
Section: Three-dimensional Assemblies Mediated By Moldsmentioning
confidence: 99%
“…Vakarelski et al demonstrated formation of gold wires in am acroscale connected network using ac olloidal mask of latex beads. [36][37]45] Importantly,t he addition of surfactant was important to stabilize the liquid film and allow the formation of the plasmonic network upon drying (Figure 4A,B). In order to improvet he reproducibility and versatility,t he authors used ap hotoresist as am askt od irect the drying of the goldc olloid ( Figure 4C).…”
Section: Three-dimensional Assemblies Mediated By Moldsmentioning
confidence: 99%
“…Vakarelski's group observed the phenomena of different liquid bridge network formations by a gold NP-suspended solution on a latex particle self-assembly as templates. [118,119] Then, an gold NPs aqueous suspension was doped on the template and deposited on the substrate: a connected liquid bridge network formed between the substrate and the latex particles and guided the gold NPs deposited in certain distribution. The effect of surfactants and surface tension displays crucial roles on the stability and formation of the initial liquid bridges.…”
Section: Evaporative Lithographymentioning
confidence: 99%
“…0.6–1 wt%, liquid films were inclined to break in the gaps among the micropillars (Figure S1a‐c). Thus, discontinuous liquid bridges have been generated connecting neighboring micropillars (Figure S1e), which have been systematically studied by several reports 8–13. Due to the diverse gap values in horizontal/vertical directions, the as‐prepared microwires preferred to form perpendicularly (The details of vertical microwire formation can be found in the Section One and Figure S2 in Supporting Information).…”
mentioning
confidence: 96%
“…Then, order‐packed polystyrene (PS) spheres have been utilized to serve as the wetting defect points for pining the liquids and guiding their rupture 8, 9. The liquid films are inclined to break regularly in the gaps among PS spheres, yielding a variety of fully connected, symmetrical microwire network.…”
mentioning
confidence: 99%
See 1 more Smart Citation